2017
DOI: 10.17957/ijab/15.0404
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Vegetable Grafting in Pakistan: Current Status, Challenges and Opportunities

Abstract: In Pakistan vegetables are grown on fairly a large area and help to fulfill the food requirements of increasing population. The average yield of vegetables in Pakistan is lower compared with the other vegetables growing countries; several reasons contribute towards this low yield such as biotic factors (diseases and pest attack), abiotic factors (low and high temperature stress, high light intensity, water scarcity, and salinity), seed quality, and potential of local vegetable's cultivars. Vegetable grafting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…The improvement of NUE efficiency is required, and the use of rootstocks has been reported to enhance the NUE in different fruit and vegetable crops, including watermelon [4,15,17,21,36,[40][41][42]. In this study, we observed that the N uptake efficiency, N utilization efficiency, and N use efficiency of watermelon was altered by the use of wild watermelon rootstocks (Figure 3a-c).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The improvement of NUE efficiency is required, and the use of rootstocks has been reported to enhance the NUE in different fruit and vegetable crops, including watermelon [4,15,17,21,36,[40][41][42]. In this study, we observed that the N uptake efficiency, N utilization efficiency, and N use efficiency of watermelon was altered by the use of wild watermelon rootstocks (Figure 3a-c).…”
Section: Discussionmentioning
confidence: 66%
“…NUE of grafted transplants is dependent on the genetic potential of the scion and the rootstock, and their interaction. Rootstocks improve the ion uptake in several plant species [4,[16][17][18][19][20][21][22]. Selection of an appropriate rootstock for a specific scion cultivar is important in order to enhance water and ion absorption, nutrient use efficiency, and plant growth and yield [23,24].…”
mentioning
confidence: 99%
“…The chlamydospores of Fon can survive for as long as 8 years in the soil and the intensive cultivation of watermelon on limited agricultural lands causes Fon to persist longer in fields, making the control of Fon difficult [2]. Different methods, such as disease-resistant cultivars [3], grafting [4,5] and intercropping [6] were utilized to overcome Fusarium wilt of watermelon.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous cultivation of cucumber on the same piece of land is a major hindrance for the further development of cucumber industry [12]. Grafting is an important technique in a modern vegetable production system because it provides resistance against soil-borne diseases leading towards increased yield [13][14][15]. At present, grafting is widely used to alleviate the obstacles caused by continuous cropping of cucumber, but the production of grafted transplants takes time, resources, and it is labor intensive [16,17].…”
Section: Introductionmentioning
confidence: 99%